Soil microbial processes and resource limitation in karst and non-karst forests - Chen, Hao; Li, Dejun; Xiao, Kongcao; Wang, Kelin (Functional ecology, 2018)
Soil micro‐organisms play a key role in soil biogeochemical cycles, but their growth and activities are often limited by resource availability. Understanding soil processes that are driven by micro‐organisms and resource limitation of microbes will help to elucidate controls on soil fertility and improve the ability to predict the responses of an ecosystem to global changes. As a widespread ecosystem type, karst ecosystem develops from limestone or dolomite with unique soil; however, karst ecosystems remain poorly understood regarding their soil microbial processes and microbial resource limitation. Here, ecoenzymatic stoichiometry was used as an indicator of microbial resource limitation, and to model major microbial processes (i.e. decomposition of soil organic carbon and microbial respiration) in a karst and a non‐karst forest. Results showed that the modelled decomposition and respiration rates were significantly higher in the karst forest than in the non‐karst forest. In addition, results of ecoenzymatic stoichiometry showed that the karst forest was more carbon‐limited than the non‐karst forest. In contrast, the karst forest was likely saturated with nitrogen, but the non‐karst forest was limited by nitrogen. Both the karst and non‐karst forests were limited by phosphorus, but phosphorus deficiency was more evident in the non‐karst forest than in the karst forest. These findings highlight the specific profiles of karst ecosystems, and they suggest that the responses of karst ecosystems to global changes should be very different compared to other ecosystems. A plain language summary is available for this article. Plain Language Summary